Dynamic service reconfiguration with multi-agent systems - Rodrigues, Nelson (2018)
Most modern manufacturing systems rely on constantly seeking new solutions to better fulfil their manufacturing objectives. As reported in today’s manufacturing literature, dynamic service reconfiguration is one solution that permits to endorse continuous service reconfiguration, flexibility and evolvable systems. In spite of the current research efforts, real reconfiguration solutions are still lacking automated tools that support dynamic and runtime reconfigurations by discovering new adaptation needs and opportunities and, thus, explore possible actions leading to new system configurations. To overcome these issues, it is essential to provide solutions that answer to the “when” and “what” to reconfigure questions. Most of the service changes triggers rely on reactive events, where decisions come from a centralized decision-maker and are performed manually. Based on these facts a service-oriented multi-agent systems architecture is described aiming at actively promoting service reconfiguration (e.g., improvement of the service’s properties and/or update the services’ catalogue) to cope with the unexpected and unpredictable condition changes. This paper describes the processes that decide which service reconfiguration should be applied to each circumstance. The developed prototype for a flexible manufacturing system case study allowed verifying the feasibility of the proposed dynamic service reconfiguration solution in different scenarios.